A loop‐mediated isothermal amplification assay for the diagnosis of pulmonary tuberculosis. (1st March 2019) - Sharma, G.; Tewari, R.; Dhatwalia, S.K.; Yadav, R.; Behera, D.; Sethi, S.
Abstract: Quantitated Mycobacterium tuberculosis ( M.tb ) H37Rv DNA was used to analyse the sensitivity and the specificity was assessed using DNA isolated from the reference strain H37Rv, 12 nontuberculous mycobacterium (NTM) species and five nonmycobacterium species. Furthermore, performance of the assay was evaluated on the sputum samples and compared with smear microscopy, culture and PCR. mpt64 (also called mpb64 or Rv1980c) loop‐mediated isothermal amplification (LAMP) successfully detected 1 pg DNA within 40 min and successfully rejected NTMs and other bacterial species tested. It specifically detected all the 119 confirmed TB cases and 100 of the 104 control cases. The resulting sensitivity and specificity of LAMP assay was found to be 100% (95% CI: 96·79–100%) and 96·15% (95% CI; 90·44–98·94%) respectively. Significance and Impact of the Study: Loop‐mediated isothermal amplification (LAMP) is a technique for isothermal DNA amplification suitable for cost‐limited settings as it prevents the use of sophisticated instruments. Using mpt64 antigenic protein gene, we developed a LAMP assay especially for organisms of the M. tuberculosis complex. mpt64 LAMP assay showed 100% sensitivity and detected all the bacteriologically and clinically positive TB cases not detected by smear, culture or PCR methods.